The Transformation of Values in A Catfish Folklore - Bahruddin, Uril; Jauhari, Qomi Akit; Faizin, Nur; Sempo, Muhammad Widus (KARSA Journal of Social and Islamic Culture, 2020)
Industrial developments have brought many significant changes in various fields of life, especially agriculture and education. It seems that the transformation of the agricultural sector and fishpond farming in Medang Village, Glagah, Lamongan are affected by the catfish folklore that keep the people concerned for generations. This is a phenomenological research and the results are descriptive and qualitative. The data are described and interpreted hermeneutically. The results indicate that the catfish folklore contains a number of educational values that dynamically developed along with the people’s beliefs about the folklore as a myth. This transformation of educational values includes: the value of ubudiyyah, the value of the struggle in the life; and the moral value. This transformation occurs through the intervention of many parties, both internal and external ones, such as the local government, the elders, the community leadersÂ as well as educators. Other factors are technological development and the development of the fishery industry. This research suggests the stakeholders of the village level, districts, and regencies to make the folklore as a medium in learning the educational values. The society, especially the fishpond farmer at Medang village are suggested to preserve the folklore without preventing it to be known. The scholars and the artists can also bring this folklore to life and present it in a more interesting format, both in a pure and classic appearance and in collaboration so that it can be presented as a myth that has a profound meaning.